POLA KEPEMIMPINAN KEPALA MADRASAH DI MTS PAB-1 SAMPALI - Amiruddin Amiruddin; Sri Rahayu Nasution; Sartika Hutasuhut; Muhammad Isa; Fuad Zaini (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to reveal the leadership pattern of a madrasa head, the formulation of the problem in this study is how the leadership pattern of the madrasa head and the implementation of the madrasa head in decision making in the madrasa. This research was conducted at MTS PAB-1 Sampali, Deli Serdang Regency. The research method used in this research is to use a qualitative approach. The result of the research is that the leadership applied is a democratic leadership pattern by involving all elements of the school such as teachers, students, stake holders and parents. Decision making on students who commit disciplinary violations also goes through three stages before being sanctioned with dismissal, namely Giving Advice, Recording/Agreement Letters/Black Books, Calling Parents